Deteriorating employment and marriage decline in Japan - Shigeki Matsuda; Takayuki Sasaki (Comparative Population Studies (CPoS), 2020)
As is the case in Western countries, more Japanese are marrying later or remaining unmarried and are postponing childbearing or staying childless. Previous studies revealed that those individuals who were unable to secure regular employment due to the serious recession between the mid-1990s and mid-2000s, labelled a "lost generation," had a very low marriage rate. But what about subsequent cohorts? Using a discrete-time logit model to analyse Japanese Life Course Panel Survey data, this study investigates the effects of employment on first marriages between 2007 and 2015, including cohorts after the lost generation. The results indicate that: (a) among men who are classed as non-regular employees, unemployed, or low-income regular employees, the likelihood of first marriage is low due to their weak economic position; and (b) women have a low likelihood of first marriage if they are non-regular employees or unemployed, not because of their employment status but because they have less chance of meeting a romantic partner and also because of their values regarding work and marriage. These explicit gender differences in the findings contradict observations made in contemporary Europe and North America, where a trend towards gender convergence in the effects of employment and earnings on marriage has been identified. The ambivalence towards gender equality in family and the workplace will be discussed to understand why many young Japanese remain single.
urn:nbn:de:bib-cpos-2020-22en0
Keywords: 300; Marriage; Low fertility; Employment; Romantic partner; Values